Analisis Pengaruh Standar Operasional Prosedur, Teknologi Informasi, dan Pengawasan Terhadap Kinerja Karyawan (Studi Kasus pada PT. Fore Coffee Malang) - Setyawati, Dyah; N, Nathania Salwa; A, Natasha Lia; Juhadi, Nandha; Rozikin, Moch Nur; F, Alpha Deepny (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this research is to evaluate the impact of standard operating procedures (SOP), information technology, and supervision on employee performance at PT. Fore Coffee Malang. This study utilizes a quantitative data method with multiple linear regression, obtained from primary data of respondents. Sampling is carried out through purposive sampling technique involving 48 employees at PT. Fore Coffee Malang. Data analysis involves scale range, classical assumption tests, multiple linear regression tests, and hypothesis testing such as t-test and F-test. The results of the research indicate that standard operating procedures (SOP) and information technology have a positive and significant impact, while supervision has a positive but insignificant impact on employee performance at PT. Fore Coffee Malang. In conclusion, the implementation of standard operating procedures (SOP), information technology, and effective supervision can influence employee performance, with the potential to enhance company productivity.